Analisis Keberagaman Agama dan Meningkatkan Kerukunan Bermasyarakat dan Sikap Toleransi di Desa Pijor Koling - Ayu Ashara Harahap; Epa Purnama Sari Harahap; Intan Fitri Panisa Harahap; Halimah Safitry Al-Fauziah; Masdelima Hasibuan; M. Fakhriza6; Nurkhofifah Nasution; Yuli Anisyah Hasibuan (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
In Indonesia, tolerance of religious life has become a special concern because until now there are many cases that show the frequent occurrence of conflicts in the name of religion in various regions. This diversity can be seen in Pijor Koling Village where there are 2 formal religions, namely Islam and Christianity, which can coexist for quite a long time. This research was carried out in Pijor Koling Village, Dolok District, North Padang Lawas Regency. The method used in this research is a qualitative research method. The data collection was carried out by means of observation and in-depth interviews with a number of informants. The results obtained were that the people of Pijor Koling Village respected and respected each other without discriminating against each other. The mutual support among the people of Pijor Koling is very real. In major religious holidays, the people of Pijor Koling stay in touch with each other, keep each other safe when worshiping in celebration of the holiday. Prioritizing one's own religion but not putting aside the religion or beliefs of others. Keywords: Religious Diversity, Tolerance